2019
DOI: 10.11648/j.edu.20190801.13
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Mainstream Schooling and Shadow Education in English Language Teaching: A Case Study in Hong Kong

Abstract: In this article, the writers employ the Service Quality Gap Model to investigate a social phenomenon that has existed for decades but has taken off recently -Supplementary Education. Being a billion-dollar industry that reaches more than three quarters of students in prominent countries, it has a tangible influence on our education system. By comparing the first three stages of the model with interview recordings with students and teachers, the writer explores the differences between perceptions of the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In previous research, tutored students mainly reported gains in terms of knowledge (Kim, 2016), skills (Kwok, 2004;Nam & Chan, 2019), and attitudes (Hajar, 2018). Despite these initial empirical findings, existing research has not yet provided a clear picture of the experienced benefits of shadow education attendance, particularly because such benefits differ from student to student.…”
Section: Experienced Benefitsmentioning
confidence: 95%
See 2 more Smart Citations
“…In previous research, tutored students mainly reported gains in terms of knowledge (Kim, 2016), skills (Kwok, 2004;Nam & Chan, 2019), and attitudes (Hajar, 2018). Despite these initial empirical findings, existing research has not yet provided a clear picture of the experienced benefits of shadow education attendance, particularly because such benefits differ from student to student.…”
Section: Experienced Benefitsmentioning
confidence: 95%
“…Research on students' experienced benefits of attending shadow education has revealed varying preferences in terms of tutor focus. Whereas some students appreciate that tutors focus on content-related subject knowledge (Nam & Chan, 2019;Paramita, 2014), others value tutors that focus on memorising answers to questions listed in textbooks (Tsai & Kuo, 2008), or predicting exam questions (Nam & Chan, 2019). In most cases, students seem to experience the benefits of shadow education when tutors focus on lesson revision or on handling examination time and questions (Kwok, 2004).…”
Section: Shadow Education Adding To or Substituting For Home And Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many parents trust SE as a helper and a complement to formal education (Bray, 2014). SE follows the development of education around the world and is spreading worldwide (Nam & Chan, 2019). However, it does not focus on simple cognitive aspects.…”
Section: Introductionmentioning
confidence: 99%
“…While the teachers regarded tutoring as a supplement to teaching, they also criticized tutoring for distorting the purpose of education which is supposed to promote whole-person development. Nam and Chan (2019) observed the relationship between schools and tutoring of English subject. It was found that both schooling and tutoring are involved in working mutually to cover each other's weaknesses as students' individuality and an abundance of resources can be used to improve their English.…”
Section: Introductionmentioning
confidence: 99%